Further records of species of Gennadas (Crustacea, Decapoda, Dendrobranchiata, Benthesicymidae) in the Mexican Pacific - Hendrickx, Michel E. (Zootaxa, 2015)
Additional material of species of Gennadas was collected off western Mexico during the TALUD survey aboard the R/V "El Puma". Gennadas sordidus was by far the most common species collected and only a few specimens of the other three species, G. incertus, G. propinquus and G. scutatus, were obtained. New and previous records indicate that Gennadas sordidus is widely distributed along the west coast of Mexico, although there is only one record for it south of the Gulf of California. In this study it was collected in as many as 35 localities, both in the Gulf of California and off the west coast of Southern Baja California. Numbers of specimens also confirmed that it is the dominant species of Gennadas in the area. Gennadas incertus was found in six samples, all from off the west coast of northern Baja California. The other two species occurred each in two samples only, with sampling localities widely spread along the Baja California Peninsula. Compared with the rest of the eastern Pacific, the diversity of Gennadas in Mexican waters is intermediate (6 species) vs. 9 in Chile and 4 in the NW Pacific.